Representation of Indonesia’s Judiciary of Ahok’s Blasphemy Verdict in The New York Times Article: A Critical Discourse Analysis - Hasna Nurhaliza; Trisnowati Tanto (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
This paper comprises the analysis of the representation of Indonesia’s judiciary through Ahok’s blasphemy verdict in The New York Times article entitled “‘Rot at the Core’: Blasphemy Verdict in Indonesia Dismays Legal Experts”. The research belongs to Critical Discourse Analysis (CDA), which van Dijk (2015) describes as a study of how social-power abuse and inequality are conveyed, reproduced, legitimated, and resisted by text and talk in the social and political context (p. 466). The analysis will focus on the micro-level analysis which covers three aspects of analysis, namely macrostructures, microstructures, and superstructures. This paper uses a qualitative descriptive method, which requires the analyst to observe and describe the data in order to show the representation. Throughout the analysis, it is shown that Indonesia’s judiciary is represented negatively in the news article.